Is the Catholic Church’s pilgrimage toward holiness a human reality or God’s grace? (Hekima Review, 2016)
Although the question of grace and sin seems complex in the theological discourses of most theologians, it can simply be understood in the manner the pilgrim Church has been journeying in faith towards holiness. ough entangled by sin committed by her faithful, the graces of God enable her to overcome grave challenges—as the bride the Church has been faithful to her groom, Christ. It is not because she does merit any of the God’s gifts but it is due to God’s overflowing goodness which extends toward her. Indeed, it is a challenging invitation for the Church as she has look into her past with gratitude in order to reshape the present and optimistically envisage the future.